2012
DOI: 10.1080/00207543.2012.677864
|View full text |Cite
|
Sign up to set email alerts
|

A reactive GRASP and Path Relinking for balancing reconfigurable transfer lines

Abstract: A line balancing problem for reconfigurable transfer lines with sequence-dependent setup times and parallel machines was studied. These lines are paced and serial, i.e. a part to be machined passes through a sequence of stations. Stations are composed of CNC (Computer Numerical Control) machines. At least one CNC machine is installed at each station. These CNC machines are mono-spindle head machines, hence setup times between operations have to be taken into account. The origins of setup times are various, for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 46 publications
(50 reference statements)
0
12
0
Order By: Relevance
“…The use of metaheuristics for solving the computationally complex NP-hard optimization problems is significantly growing because of its effectiveness of getting the near optimal solutions in a reasonable time (Hauser and Chung 2006;Bachlaus et al 2009;Borisovsky et al 2009;Pal et al 2011;Essafi et al 2012;Lee 2017 (Blum 2005).…”
Section: Solution Methodsmentioning
confidence: 99%
“…The use of metaheuristics for solving the computationally complex NP-hard optimization problems is significantly growing because of its effectiveness of getting the near optimal solutions in a reasonable time (Hauser and Chung 2006;Bachlaus et al 2009;Borisovsky et al 2009;Pal et al 2011;Essafi et al 2012;Lee 2017 (Blum 2005).…”
Section: Solution Methodsmentioning
confidence: 99%
“…The number of identical parallel workstations (machines or workers) employed [24], [25], [26], [27], [28], [29], [30], [31], [32].…”
Section: Line Layout Design and Balancingmentioning
confidence: 99%
“…This problem was considered mostly for assembly systems ( [33], [46], [47], [51]) and with equipment selection( [41], [48], [49], [50]). Recently, this problem has been also formulated for machining lines [28], [31]. Note that the setup costs introduced by [52] for a multimodel assembly line balancing problem are equivalent to equipment costs associated with the facilities required on workstations to process each type of product.…”
Section: Line Layout Design and Balancingmentioning
confidence: 99%
“…Details on the industrial application of this problem can also be found in Essafi, Delorme, and Dolgui (2012). The initial approach to solve this problem has been the use of a preprocessing procedure along with a mixed integer linear programming model (MILP) and its direct solution using CPLEX.…”
Section: Introductionmentioning
confidence: 99%